Socio-structural and direct health challenges related to illness management among patients with type 2 diabetes in Kenya and Tanzania during the COVID-19 pandemic: A qualitative inquiry. - Sally Mmanyi Mtenga; Irene Mashasi; Lyagamula Kisia; Peter Binyaruka; Honorati Masanja; Shukri F Mohamed; Richard E Sanya; Grace Mhalu; Grace Magembe; Kaushik Ramaiya; Gershim Asiki; Frances Mair; et al. (PLOS Global Public Health)
During COVID-19, people with type 2 diabetes (T2D) experienced increased vulnerability, including severe COVID-19 complications, disruptions in diabetes management, and social isolation. These aspects were heightened in many sub-Saharan African countries, such as Kenya and Tanzania, where healthcare systems already face critical challenges in coping with increasing non-communicable diseases (NCDs). Little is known about how people with T2D in these countries managed their diabetes or how the different approaches to COVID-19 control (Kenya imposed lockdown and curfew, whereas Tanzania adopted less strict measures) impacted their T2D management. This qualitative study aimed to compare the accounts of T2D patients in both countries to examine similarities and differences in the illness management challenges they faced during the COVID-19 pandemic.Semi-structured interviews were conducted with 52 patients (Kenya, n=22; Tanzania, n=30), and the transcripts were analyzed thematically. Despite different COVID-19 control measures, patients in both countries faced similar direct health challenges, such as difficulties accessing diabetic consultations and treatment, but they also experienced distinct socio-structural challenges. Direct health challenges included difficulties in accessing diabetic consultations and treatment, limited availability of diabetic medicine at health facilities and mental health distress. These were exacerbated by socio-structural challenges, many of which pre-dated COVID-19 but intensified during the pandemic. These included closure of diabetic clinics in Dar es Salaam, business instability, financial difficulties, health insurance challenges, higher food prices impacting patients' adherence to T2D dietary recommendations (in both countries), and price inflation of diabetic medicine and test kits (in Kenya). Together, these challenges led to patients practicing self-medication, missing doses and resulted in poor blood sugar control. People with T2D in Kenya and Tanzania have described similar illness management challenges. In both countries, future contingency planning is essential to ensure adequate routine management of T2D and to improve access to care in emergency situations. Affordable comprehensive health insurance, economic support, and psychosocial services are required to increase patient resilience and support the health and wellbeing of people with T2D.